Investment policy in the tourism sector of Kazakhstan - Nasyrkhanov, A.D.; Iskakov, B.M. (BUKETOV BUSINESS REVIEW, 2020)
Object:The object of the study is to develop a set of methodological, scientific and practical recommendations on ensuring the investment attractiveness of the tourism sector in Kazakhstan. Methods:Methods of economic and comparative analysis, classification were used in this article, economic and statistical methods were used to process information. Results:The results of the study confirm the effectiveness of tourism development in the context of globalization. The Republic of Kazakhstan is an attractive country for investing not only in raw materials production, but also in the service sector. Over the years of independence, the economy of Kazakhstan has risen significantly, the well-being of the people has increased, and the quality oflife has noticeably improved. Kazakhstanis began to pay more attention to the quality of leisure. Thus, the tourism industry has been singledout as a separate promising cluster of the republic, because Kazakhstan has the potential to develop this cluster. Conclusions:The article discusses the problems and prospects of the development of investment policy in the tourism industry. The authors identified the main directions of state participation in the investment process, aimed at the development of the tourism sector. The authors analysed scientific approaches to certain problems of the development and functioning of the tourism industry. Conclusions are drawn on the possibility of applying foreign experience in the tourism industry of Kazakhstan.